2019
DOI: 10.4239/wjd.v10.i3.224
|View full text |Cite
|
Sign up to set email alerts
|

Optimized health care for subjects with type 1 diabetes in a resource constraint society: A three-year follow-up study from Pakistan

Abstract: BACKGROUNDInadequate health infrastructure and poverty especially in rural areas are the main hindrance in the optimal management of subjects with type 1 diabetes (T1D) in Pakistan.AIMTo observe effectiveness of diabetes care through development of model clinics for subjects with T1D in the province of Sindh Pakistan.METHODSA welfare project with name of “Insulin My Life”, was started in province of Sindh, Pakistan. This was collaborative work of Baqai Institute of Diabetology and Endocrinology, World Diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Recent data has highlighted increasing trends in the incidence of type-1 DM. 18 We observed that neuropathy was the most frequent complications observed in 45.5% DM patients while gastrointestinal, cardiac and renal complications were observed in 15.5%, 9.5% and 9.5% DM patients respectively. A study done by Lakhair MA et al among newly diagnosed type-2 DM patients revealed 32.7% patients to have peripheral neuropathy at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 61%
“…Recent data has highlighted increasing trends in the incidence of type-1 DM. 18 We observed that neuropathy was the most frequent complications observed in 45.5% DM patients while gastrointestinal, cardiac and renal complications were observed in 15.5%, 9.5% and 9.5% DM patients respectively. A study done by Lakhair MA et al among newly diagnosed type-2 DM patients revealed 32.7% patients to have peripheral neuropathy at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 61%
“…2 According to the International Diabetes Federation (IDF), in the year 2015, Pakistan witnessed over 7 million recorded instances of diabetes, with around 2% of those individuals being afflicted with Type 1 Diabetes (T1D). 3 The reported incidence of Type 1 Diabetes (T1D) in Pakistan is 1.02 per 100,000 individuals annually. 4 A multitude of environmental exposures are believed to significantly contribute to the onset of Type 1 Diabetes (T1D).…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Diabetes Federation Atlas 9th edition 2019 estimates, around 1.98 billion children (0-14 years) and 2.58 billion adolescents (0-19 years) have type 1 diabetes globally [ 2 ]. In Pakistan, the incidence of T1DM has been reported to be 1.02 per 100,000 per year [ 3 ]. As the incidence of this disease is increasing worldwide, diabetic complications have come to represent a major concern despite the advances in treatment.…”
Section: Introductionmentioning
confidence: 99%